Contrasting reactivity of anionic boron- and gallium-containing NHC analogues: E-C vs. E-M bond formation (E = B, Ga). - Protchenko, A; Saleh, L; Vidovic, D; Dange, D; Jones, C; Mountford, P; Aldridge, S (2010)
The anionic Group 13 NHC analogues [(CHNDipp)(2)E](-) (E = B or Ga) display contrasting reactivity towards the half-sandwich titanium imido complex Cp*TiCl(NtBu)py; while the gallium system undergoes salt metathesis yielding the first example of a titanium gallyl compound, the more nucleophilic boryl anion generates a dearomatized pyridyl fragment via attack at the ligand 2-position.